2002
DOI: 10.1177/000313480206800108
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Esophageal Perforation: Role of Esophageal Conservation in Delayed Perforation

Abstract: Definitive repair of esophageal perforation is considered the preferred treatment for patients presenting early (<24 hours). However, the optimal management of delayed presentation (>24 hours) has not been well defined. This study examined the management of esophageal perforation and compared the outcomes of early versus delayed presentation. Records of patients admitted with the diagnosis of esophageal perforation were reviewed. Contrast studies were used to confirm the diagnosis in all cases. Patient d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…The literature search yielded 1,142 studies. After review, 75 studies [2, 7–80] were found to be pertinent to this issue, with sources of information on 2,971 patients undergoing any treatment of esophageal perforation (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…The literature search yielded 1,142 studies. After review, 75 studies [2, 7–80] were found to be pertinent to this issue, with sources of information on 2,971 patients undergoing any treatment of esophageal perforation (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…In individual cases, this indication was extended for longer than 24 h for smaller lesions. Moreover, to back up this finding excellent results have been reported for using this technique [11, 12, 18, 20, 24, 27, 29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…Para plantear una reparación primaria del esófago se deben cumplir varios requisitos como son un esófago previamente sano, lograr un debridamiento completo del tejido comprometido alrededor de la perforación que generalmente se logra en perforaciones con menos de 24 horas de evolución, realizar una técnica adecuada y lograr un correcto drenaje e irrigación del área contaminada [21][22][23][24][25][26] . Ya que esta técnica conlleva una alta morbilidad principalmente debido a su alto porcentaje de fístulas, se han ideado distintas técnicas de refuerzo de la sutura con parches sintéticos o con tejido vecino vital como son los colgajos musculares o pleurales entre otros 21, 22 .…”
Section: Tratamiento Quirúrgicounclassified